The afterlives of Egyptian history : reuse and reformulation of objects, places, and texts : a volume in honor of Edward L. Bleiberg - Barbash, Yekaterina,; Cooney, Kara,; Bleiberg, Edward, 1951- (The American University in Cairo Press, 2021)
"Egypt has a particular longue durée, a continuity of preservation in deep time, not seen in other parts of the world. Over the centuries, ancient buildings have been adopted for purposes that differed from the original. Temple sites have been transformed into places of worship for new deities or turned into houses and tombs. Tombs, in turn, have been adapted to function as human dwellings already in the Late Antique Period. The Afterlives of Egyptian History expands on the traditional academic approach of studying the original function and socio-political circumstances of ancient Egyptian objects, texts, and sites to examine their secondary lives by exploring their reuse, modification, and reinterpretation. Written in honor of the Egyptologist, Edward Bleiberg, this volume brings together a group of luminous scholars from a wide range of fields, including Egyptian archaeology, philology, conservation, and art, to explore the historical circumstances, as well as political and economic situations of people who have come into contact with ancient Egypt, both in antiquity and in more recent times"--